Commercial history of Dhaka - Hassan, Delwar (Dhaka Chamber of Commerce and Industry, 2008)
Published on the occasion of the golden jubilee celebrations of Dacca Chamber of Commerc & Industry; contributed articles; covers the period, 17th to 20th century; publication is supported by IFC Bangladesh Investment Climate Fund.